Statistical Profile Districts of India - Planning Commission (Planning Commission, 1974)
It is natural that in a democratic society. the problem oi regional imbalances and pockets of backwardness should be a matter of serious concern to all people concerned with planning and economic development. In successive Five Year Plans, various measures have been introduced to accelerate the development of backward areas. These efforts have, however, yielded limited results so far mainly because of the absence of detailed planning at the local level. In the Fifth Five Year plan considerable stress has. therefore, been laid on detailed work at the district level for the collection and the analysis of relevant data and the formulation of appropriate strategies o£ development. For this, a framework of information is absolutely essential. The Multilevel Planning Section in the Planning Commission has, therefore. Initiated work on the collection and collation of district data on selected indicators. The will involve a great deal of laborious work and it will be sons’, time before comprehensive information not only about the levels of development but also about the availability and quality of resource potentials, economic infrastructure and social services will become available .
Multilevel Planning Section Planning Commission Government of India
Government of India Planning Commission
Keywords: Demography; Urban Series; Rural Series; Agriculture; Infrastructure; Banking Data; statistical profile Districts OF India; Negligible